Electrospun luminescent piezo webs as self-powered sensing platform for small accelerations at low frequency. (August 2020) - Huang, Xi; Jin, Long; Wang, Chuanfeng; Xu, Yali; Peng, Zhou; Xie, Meilin; Zhang, Chaoliang; Yang, Weiqing; Lu, Jun
Abstract: The sensitive detection of low frequency small accelerations is particularly desirable in seismic prediction, wave energy utilization and dam/bridge damage monitoring. In this work, we report for the first time the electrospinning of polyvinylidene fluoride/carbon dots (PVDF/CDs) nanofibers and their piezoresponse under different acceleration rate. The desirable nanofibrous mats, with thin and smooth morphology, are acquired by changing spinning parameters, and β-phase crystal content is improved with increasing introduction of CDs. At an acceleration rate of 6 m/s 2, frequency of 1.6 Hz and applied force of 35 N, the maximum open-circuit voltage density of 55.6 V cm −3, and short-circuit current density of 2.1 μA cm −3 are achieved for PVDF/CDs fiber with 1% (wt/v) CDs loading. In particular, the fiber mat is tested with detection sensitivity of acceleration change up to 0.4 m/s 2 for potential as an acceleration sensor. Moreover, CDs not only improve the piezoresponse of PVDF fiber, but also endow the substrate with multifluorescence performance. The as prepared fiber could be used as active layer to perceive the prevalent small acceleration changes at low frequency, such as those from earthquake, tidal flow, ocean waves, reservoir dams, railway bridges, and so on. Highlights: Electrospinning of multifluorescent polyvinylidene fluoride/carbon dots nanofibers. Piezoresponse enhancement of nanofibrous polymers by introduction of carbon dots. Sensitive detection of low frequency small accelerations with luminous piezo webs.